Debt Policy, Investment Policy, and Dividend Policy as Determinants of Firm Value: Evidence From Banking Companies Listed on The Indonesia Stock Exchange - Ni Kadek Ayu Sugiantari; I Wayan Widnyana; Gregorius Paulus Tahu (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
Financial management refers to the activities carried out by an organization to plan its finances, manage assets, hold funds, and control the company’s assets or funds. Enterprise value is one of the key indicators used by investors to assess a company’s prospects. Enterprise value, as reflected in the stock price, is naturally influenced by several factors such as stock price indices, interest rates, and the company’s fundamental conditions. A company’s value can be calculated using the Price-to-Book Value (PBV) ratio. The Price-to-Book Value (PBV) ratio is a calculation or comparison between a stock’s market value and its book value. Using this PBV ratio, investors can immediately determine how many times a stock’s market value is priced relative to its book value. The researcher examined the effects of debt policy, investment policy, and dividend policy on the firm value of the banking sector listed on the Indonesia Stock Exchange. The sample size used in this study was 55 observations. Sampling in this study was conducted using purposive sampling. The data analysis technique used was multiple linear regression analysis. The results of this study indicate that debt policy has a positive effect on firm value, investment policy has a positive effect on firm value, and dividend policy has no effect on firm value.